2022
DOI: 10.3390/s22249815
|View full text |Cite
|
Sign up to set email alerts
|

UV-Light-Tunable p-/n-Type Chemiresistive Gas Sensors Based on Quasi-1D TiS3 Nanoribbons: Detection of Isopropanol at ppm Concentrations

Abstract: The growing demand of society for gas sensors for energy-efficient environmental sensing stimulates studies of new electronic materials. Here, we investigated quasi-one-dimensional titanium trisulfide (TiS3) crystals for possible applications in chemiresistors and on-chip multisensor arrays. TiS3 nanoribbons were placed as a mat over a multielectrode chip to form an array of chemiresistive gas sensors. These sensors were exposed to isopropanol as a model analyte, which was mixed with air at low concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…When TiS 3 is incorporated into the films, their resistance increases but the sensor response remains qualitatively the same; see Figure b. Interestingly, sensors based on pure TiS 3 also exhibit resistance increase upon their exposure to alcohols, so in Ti 3 C 2 T x -TiS 3 devices both components contribute to the observed sensor response at room temperature. The 75 wt % Ti 3 C 2 T x /25 wt % TiS 3 sensors showed a stable response to ethanol over the course of several days, as illustrated in Figure S1 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…When TiS 3 is incorporated into the films, their resistance increases but the sensor response remains qualitatively the same; see Figure b. Interestingly, sensors based on pure TiS 3 also exhibit resistance increase upon their exposure to alcohols, so in Ti 3 C 2 T x -TiS 3 devices both components contribute to the observed sensor response at room temperature. The 75 wt % Ti 3 C 2 T x /25 wt % TiS 3 sensors showed a stable response to ethanol over the course of several days, as illustrated in Figure S1 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 90%
“…Because of the weak interactions between these 1D chains, TiS 3 crystals typically exfoliate in the form of high-aspect-ratio nanoribbons with their long axes corresponding to the crystallographic b direction of TiS 3 . Overall, TiS 3 could be a promising material for gas sensor applications because of its semiconductor properties with a bandgap of ∼1 eV, very high theoretically predicted mobility, , highly anisotropic electronic and optoelectronic properties, and intriguing low-temperature physics. Several recent studies investigated solution exfoliation of TiS 3 and its applications in photodetectors, printed electronics, and gas sensing . In this study, we specifically focused on TiS 3 in combination with Ti 3 C 2 T x and found that the TiS 3 -Ti 3 C 2 T x sensors exhibit several improved characteristics compared to the sensors based on the pristine MXene material.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of their small thickness, the exfoliated TMTC flakes can be used for the measurements of gate-dependent electrical properties, which in recent years have gained significant interest in the case for TiS 3 [7][8][9][10][11][12][13][14][15][16] and, to a lesser extent, for ZrS 3 . [17][18][19] In particular, electrical measurements of TiS 3 revealed many interesting characteristics, such as an n-type transport, [7][8][9] a gate-dependent metal-insulator transition around 220 K, 13 gas sensing properties, 20 and a possible access to charge density wave physics at low temperatures. 2,10,15,21 Compared to TiS 3 and ZrS 3 , there were fewer studies on field-effect measurements on exfoliated HfS 3 flakes, 22,23 and some of the basic electronic properties of this material, such as its electrical conductivity and charge carrier mobilities, have not been reported as yet.…”
Section: Introductionmentioning
confidence: 99%